Fear and loathing in the benthos: Responses of aquatic insect larvae to the pesticide imidacloprid in the presence of chemical signals of predation risk - Pestana, João L. T.
The influence of interactions between pesticide exposure and perceived predation risk on the lethal and sub-lethal responses of two aquatic insects was investigated using the pesticide imidacloprid, and a combination of predator-release kairomones from trout and alarm substances from conspecifics. Laboratory experiments examined feeding and respiration rates of the caddisfly Sericostoma vittatum as well as the growth, emergence and respiration rates of the midge Chironomus riparius, exposed to sub-lethal concentrations of imidacloprid. The effects of the two stressors on burrowing behaviour of both species were also assessed. The results show significant effects of environmentally relevant concentrations of imidacloprid on all endpoints studied. Perceived predation risk also elicited sub-lethal effects in C. riparius and S. vittatum, the latter species being less responsive to predation cues. The effects of simultaneous exposure to both types of stressors were assessed using two different approaches: analysis of variance and conceptual models [concentration addition (CA) and independent action (IA)] normally used for the evaluation of contaminant mixture exposure. Both statistical approaches showed no significant interactions on responses in simultaneous exposures in the majority of parameters assessed with only a signification deviation from the reference CA and IA models being found for C. riparius respiration data contrary to the ANOVA results. Exposure to imidacloprid also compromised antipredator behavioural responses of both insect species, with potential negative consequences in terms of mortality from predation in the field. The results obtained demonstrate that natural and anthropogenic stressors can be treated within the same framework providing compatible data for modelling. For an improved interpretation of ecological effects it will be important to expand the mechanistic study of effects of combined exposure to pesticides and perceived predation risk by measuring different endpoints over a wider range of pesticide concentrations. (C) 2009 Elsevier B.V. All rights reserved.